The Incidence Trend of Type 1 Diabetes among Children and Adolescents 0-14 Years of Age in the West, South, and Tripoli Regions of Libya (2009-2018) - Rowida M. Khashebi; Christopher C. Patterson; Mostafa S. Shebani (Galenos Yayincilik, 2023)
INTRODUCTION: To estimate the incidence rates (IR) and analyse the trend in type 1 diabetes (T1D) among children aged 0-14 years in the West, South, and Tripoli regions of Libya. METHODS: A retrospective study was conducted on Libyan children aged 0-14 years with a new diagnosis of T1D who were admitted and/or had their follow-up at Tripoli Children's Hospital during the period 2004 to 2018. The data were used to estimate the IR and the age-standardized IR per 100,000 population in the studied region for the years 2009-2018. The IRs by sex and age group (0-4, 5-9, 10-14 years) for every calendar year were assessed. RESULTS: A total of 1,213 children were diagnosed during the study period (2004-2018), 49.1% were males with a male-to-female ratio of 1: 1.03. The mean age (±standard deviation) at diagnosis was 6.3±3.8 years. The distribution of incident cases according to age group 0-4, 5-9, and 10-14 years was 38.2%, 37.8%, and 24.1%, respectively. Poisson regression modelling in the period 2009-2018 revealed an overall trend of a 2.1% increase per annum. In the period 2014-2018, the overall age-adjusted IR was 31.7 (95% confidence interval: 29.2-34.2) per 100,000 population, the IRs of age groups 0-4, 5-9, and 10-14 years were 36.0, 37.4, and 21.6 per 100,000, respectively DISCUSSION AND CONCLUSION: The incidence of T1D in Libyan children in the West, South, and Tripoli regions appears to be rising, with a higher rate in the 0-4 and 5-9 year age groups.